Trade transparency and trading volume: the possible impact of the financial instruments markets directive on the trading volume of EU equity markets. (15th October 2009) - Avgouleas, Emilios; Degiannakis, Stavros
The EC Directive on financial instruments markets 2004 (MiFID) has introduced a number of order and trade publication obligations imposed on organised exchanges, alternative trading systems (ATS), and the class of broker dealers that execute transactions in shares internally. This article investigates the impact of MiFID's trade transparency rules on the trading volume of EU equity markets in a forward-looking mode. We use data extracted from the closest possible precedent and examine trading volume levels before and after trading in FTSE100 stocks on the London Stock Exchange (LSE) shifted from the quote-driven Stock Exchange Automatic Quotation System (SEAQ) to the order-driven securities electronic trading service (SETS). This change resulted in significantly increased transparency standards. Trading volume is measured on the basis of three criteria: volume-based turnover, value-based turnover and turnover ratio. No evidence is found indicating that higher transparency standards lead per se to higher levels of trading volume. Therefore, the impact of MiFID's transparency rules on trading volume in EU equity markets should become a matter of further study following their implementation.